The Comprehensive Sourcebook of Bacterial Protein Toxins - Alouf, Joseph E;Ed. Popoff Michel R;Ed (Elsevier, 2006)
Bacterial toxins play an important role in infectious diseases. Several are amongst the most potent biological agents known to man. Cholera, pertussis, botulinum, clostridium and tetanus toxins are all produced by bacteria. In many cases, it is the toxin produced and not the infectious agent itself that causes pathology. Botulinum toxin has now of course found clinical application as botox, and anthrax, and other toxins, have potentially devastating effects if misused as an agent of biological terror. This book describes the major achievements and discoveries relevant to bacterial protein toxins since the turn of the new century, illustrated by the discovery of more than fifty novel toxins (many of them identified through genome screening). The establishment of the three-dimensional crystal structure of more than 20 toxins during the same period offers deeper knowledge of structure-activity relationships and provides a framework to understand how toxins recognize receptors, penetrate membranes and interact with and modify intracellular substrates.